Study of the effect of processing techniques on the quality of galantine made from milkfish (Chanos chanos) - Pola Sabar Tumohom Panjaitan; Iman Mukhaimin; Susi Ratnaningtyas; Liliek Soeprijadi; Devi Wulansari (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Milkfish (Chanos chanos) is one of the commonly consumed fishery commodities in Indonesia. However, diversification of processed products from milkfish, such as pindang (fish brine) and soft bone milkfish, is considered too simple. Whereas, milkfish has a high nutritional content. An innovation to attract more people to consume this highly nutritious commodity is to process it into fish galantine. Milkfish galantine is processed with the basic ingredients of milkfish, bread flour, and eggs that are seasoned then molded and processed at high temperatures. The process of making milkfish galantine includes preparing milkfish as raw materials, scaling and gutting the fish, mincing the milkfish meat, mixing it with other ingredients, molding, and processing. Fish galantine is generally made through high-temperature processing, such as roasting and steaming. Different high-temperature processing techniques can affect the quality of fish galantine. Therefore, this research aimed to assess the effect of milkfish composition and different high-temperature processing techniques: roasting and steaming. The different milkfish galantine formulations in this research were made by giving different proportions of minced milkfish meat as treatments: 5%, 10%, and 15%. After that, galantines were processed by steaming. Furthermore, the formulation with the highest hedonic scale score was duplicated by processing using the roasting technique. The results of the four treatments were then tested for proximate composition, vitamins, and minerals. The results of the hedonic evaluation of milkfish galantines processed by steaming showed that milkfish galantine with 15% fish meat proportion had the highest score. The test results showed that the addition of milkfish meat caused significant differences in water, ash, total fat, carbohydrate, protein, and potassium contents. In addition, the processing technique also caused significant differences in all parameters tested.Keywords:MilkfishFish galantineSteamingRoasting